1997
DOI: 10.1037/0735-7044.111.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning and memory at defined points of the estrous cycle: Effects on performance of a hippocampal-dependent task.

Abstract: Learning based on hippocampal-dependent spatial navigation in female rats was assessed at identified points in the estrous cycle corresponding to low (estrus) and high (proestrus) circulating estrogen. With background training in water-maze procedures, rats learned the location of an escape platform in the maze in a single session of 8 training trials. A strong spatial bias for the escape platform was also evident in a probe trial used to assess retention of learning 30 min after the training session. This ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(105 citation statements)
references
References 34 publications
3
98
2
2
Order By: Relevance
“…In particular estradiol has equivocal effects on cognition, with some studies showing improvements (eg, Luine and Rodriguez, 1994;Daniel et al, 1997;Bimonte and Denenberg, 1999), whereas other studies either show no effect (eg, Berry et al, 1997;Luine et al, 1998;Fader et al, 1999) or impairments with estradiol (eg, Frye, 1995;Warren and Juraska, 1997;Wilson et al, 1999). These differential effects are likely based on dose and the different types of cognitive tasks used in which performance depends on the integrity of different brain regions.…”
Section: Introductionmentioning
confidence: 88%
“…In particular estradiol has equivocal effects on cognition, with some studies showing improvements (eg, Luine and Rodriguez, 1994;Daniel et al, 1997;Bimonte and Denenberg, 1999), whereas other studies either show no effect (eg, Berry et al, 1997;Luine et al, 1998;Fader et al, 1999) or impairments with estradiol (eg, Frye, 1995;Warren and Juraska, 1997;Wilson et al, 1999). These differential effects are likely based on dose and the different types of cognitive tasks used in which performance depends on the integrity of different brain regions.…”
Section: Introductionmentioning
confidence: 88%
“…More recent in vitro studies have demonstrated that the estradiolinduced increase in spine density increases the sensitivity of the cells to N-methyl-Daspartate receptor-mediated synaptic input (28). There are a number of studies suggesting that learning ability varies over the course of the estrous cycle in female rats (29)(30)(31)(32)(33), although several other studies have not found any changes (34,35). In addition, estrogen replacement therapy appears to preserve memory function in post-menopausal women (36,37), as well as in ovariectomized female rats (38).…”
Section: Role Of Hormones In Brain Development and Cognitionmentioning
confidence: 98%
“…Under our housing conditions (absence of male rats), the estrous cycle does not synchronize, as females are kept in facilities isolated from the ones where males are kept (Schank 2001). In addition, based on the literature, the impact of the hormonal status on cognitive performance in rats is relatively negligible, and some results even show no fluctuations of performance during the cycle in the Long-Evans strain (e.g., Berry et al 1997;Stackman et al 1997). Therefore, considering the number of animals in each experimental group, estrous cycle influence on behavioral and biochemical outputs might have at best contributed to some between-subject variability in each group, but most probably not to an overall group effect.…”
Section: Subjects and Housing Conditionsmentioning
confidence: 99%